2014
DOI: 10.2298/sarh1402010p
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological effects of the initial periodontal therapy

Abstract: The results of the present study demonstrated the beneficial effects of the initial periodontal therapy on both the clinical and microbiological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[9][10][11] Furthermore, hitherto clinical experiences also show that the improvement in clinical condition in PD and in CAL, after three, six and twelve months also ensued. [12][13][14][15][16] However, with non-surgical therapy it is impossible to remove all bacteria deposits. For example bacteria from deep unapproachable periodontal pockets or microorganisms from other areas of oral cavity, which are beyond the scope of non-surgical therapy, make results of this therapy to be unpredictable and dependent upon many different factors.…”
Section: Discussion:-mentioning
confidence: 99%
“…[9][10][11] Furthermore, hitherto clinical experiences also show that the improvement in clinical condition in PD and in CAL, after three, six and twelve months also ensued. [12][13][14][15][16] However, with non-surgical therapy it is impossible to remove all bacteria deposits. For example bacteria from deep unapproachable periodontal pockets or microorganisms from other areas of oral cavity, which are beyond the scope of non-surgical therapy, make results of this therapy to be unpredictable and dependent upon many different factors.…”
Section: Discussion:-mentioning
confidence: 99%
“…When co-cultivated with macrophages and epithelial cells T. f. causes the release of anti-inflammatory cytokines, chemokines, prostaglandins E. It takes about 12 days to cultivate a small colony of bacteria. Studies have shown that this periodontopathogen is found in patients with periodontitis that did not respond to treatment ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal pathogens are commensal, resident flora in periodontal micro‐ecological environments, and can be isolated from subgingival plaque from both healthy individuals and those with periodontitis 7 . Mechanical therapy can reduce the amount of bacteria; however, major pathogens can escape the treatment process, as the instruments used cannot access infected regions, especially the furcation area 8 . Subsequently, pathogens recolonize periodontal pockets and return to the pre‐treatment levels 9 .…”
Section: Introductionmentioning
confidence: 99%